Designing PISA Like Problems for West Sumatra Mathematics and Science Junior High School Teachers - ahmad fauzan; Fridgo Tasman (Pelita Eksakta, 2020)
PISA (Program for International Students Assessment) test result on 2018 put Indonesia in the 72th position of 78 countries. The report showed the importance to improve the level of students thinking ability. There are many possible ways to develop students’ thinking. One way to do that is by giving the students drill to solve PISA problems. However, this solution is difficult to implement because designing PISA problems is difficult for the teachers. Therefore, 24 junior high school mathematics and science teachers ware selected in order to give them training and workshop to improve their ability to design PISA like problems using action research methods. Three stages ware implemented in the training and workshop. First, introduction to PISA, Second, designing PISA Problems, and third, trying out and evaluating the test result. Product of the workshop are 48 PISA like problems of mathematics and 42 PISA like problems of science.